The Fornier family in the politics of Antique, 1949-1969. - Ledesma, John Ralph M. (1996.)
This is a descriptive study of the Fornier as a political family in the province of Antique. The study utilized interview and archival research as the methods of gathering pertinent data. The study found out three things: first that the Forniers gained a foothold in Antique's electoral politics through political leadership legacy, especially by Tobias; second that they were able to maintain their political dominance through patronage using government resources; and third, economic, particulary infrastructural, contributions of the Forniers in Antique. The study concludes that a political family like the Forniers of Antique can enter, and maintain its dominance when the resources of the state is at their disposal.
Thesis (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, University of the philippines in the Visayas, Miagao, Iloilo.
Keywords: Fornier (Family) -- Antique